A Population-Based Study of Postpartum Mental Health Service Use by Immigrant Women in Ontario, Canada. (November 2016) - Vigod, Simone; Sultana, Anjum; Fung, Kinwah; Hussain-Shamsy, Neesha; Dennis, Cindy-Lee
Objective: Postpartum mental disorders are twice as common among immigrant women compared to nonimmigrant women in developed countries. Immigrant women may experience barriers to access and use of postpartum mental health services, but little is known about their service use on a population level. We described postpartum mental health service use of immigrant mothers living in Ontario, Canada, comparing to a referent group of mothers who were either born in Canada or had lived in Ontario or another Canadian province since 1985. Method: Among all women in Ontario, Canada, delivering a live infant from 2008 to 2012 ( n = 450, 622), we described mental health service use within 1 year postpartum, including mental health physician visits, psychiatric emergency department visits, and psychiatric hospitalization. Adjusted odds ratios (aORs) and 95% confidence intervals (CIs) comparing immigrant women to the referent group were adjusted for maternal age, parity, income, rurality, mental health services in prior 2 years, and maternal and newborn health. Results: Immigrant women ( n = 123, 231; 27%) were less likely to use mental health services than women in the referent group (14.1% vs. 21.4%; aOR, 0.59; 95% CI, 0.58 to 0.61), including for physician-based (13.9% vs. 21.1%; aOR, 0.59; 95% CI, 0.58 to 0.61) and emergency department (0.6% vs. 1.3%; aOR, 0.63; 95% CI, 0.57 to 0.68) services. Hospitalization risk was lower among immigrants (0.20% vs. 0.33%) but became similar after covariate adjustment (aOR, 0.92; 95% CI, 0.79 to 1.06). Conclusions: Underuse of postpartum mental health services may be contributing to the high burden of postpartum mental disorders among immigrant women.